PERANAN SATUAN POLISI PAMONG PRAJA DALAM PENEGAKAN PERATURAN DAERAH DI KABUPATEN LUWU TIMUR - Haedar Djidar; Yasruddin (Journal Publicuho, 2024)
This study aims to determine the role of the Civil Service Police Unit in enforcing regional regulations in East Luwu Regency. To find out what steps the government takes in overcoming public order that occurs in the community. This study was conducted using the Normative-Empirical Legal Research Method. Basically, this research method is a combination of a normative legal approach with the addition of various empirical elements. Thus, this study emphasizes the implementation of normative legal provisions (Laws) in their application in every specific legal event that occurs in the community. The implementation of regulations to improve student discipline at the East Luwu State Islamic Senior High School is still not going well. The diversity of backgrounds and potentials possessed by students will affect the level of student obedience in complying with regulations. Obstacles to the Implementation of the Role of the Apparatus in the Civil Service Police Unit (Satpol-PP) Office, seen from the capability factor, have not supported or hindered the implementation of tasks. This occurs because they have never participated in supporting technical training related to the main tasks they carry out.